Influence of Different Drying Methods over the Biochemical Compositions of Japanese Quince (Global Journal of Science Frontier Research, 2018)
The experiment was conducted in cooperation between RIMSA-Troyan and FRDI-Plovdiv. The biochemical composition was analyzed in fresh fruits from selected (perspective) genotypes of Japanese quince. Changes in chemical indicators in dried fruits and their analogues were also studied. In order to achieve the aim, the following variants for drying of fruits were included in the experiment: by means of an alternative energy source, a heat pump, and indoor temperature. Chaenomeles fruits are characterized with low content of sugars, and relatively high amount of organic acids. The ascorbic acid amount reached up to 102 mg% in genotype 6'. There was a high content both of tanning substances - 0,542 % (genotype 1'), and pectin - 1.07% (genotype 6'). A significant increase of organic acids, tanning substances and pectin was reported in dried fruits from different variants of drying. The aim includes a comparative analysis among variants for fruit drying with regard to the degree of retaining the biochemical composition indicators.
Keywords: chaenomeles sp; japanese quince; fruits; biochemical composition; drying technologies